Sistem Informasi Pelayanan Kesehatan Gigi Pasien Umum dan Peserta BPJS pada Klinik Praktek drg. Farah Chairani - Diannisa Azhara; Ramli Ramli; Ari Usman (Universitas Harapan Medan, 2021)
The Practice Clinic of drg. Farah Chairani collected data on patient data, complaint data, care data, and cost data.In patient data, patients are divided into general patients and BPJS participants.Then in the maintenance data, it is also distinguished on the current treatment and ongoing care.The Practice Clinic of drg. Farah Chairani in the process of storing patient data, complaint data, care data, and cost data are still in paper documents.So when the patient's status card runs out, and data collection is done in a different place, the data is often lost and not found. In the process of searching for patient data, drg. Farah Chairani also took a long time. Due to having to look for data that is not in alphabetical order in data storage. As well as recording their financial reports, drg. Farah Chairani is still listed in the ledger.With the above problems, a desktop-based application was made to facilitate processing patient data, searching for patient data, and making financial reports at drg. Farah Chairani's Clinical Practice. And based on the results of trials on this information system, it can store patient data, search data, and make financial reports at drg. Farah Chairani's Practice Clinic. Keywords: Information System, Health Service, Patient Regirstration, BPJS Participants.